Analisis Manajemen Redaksi Dalam Peningkatan Kualitas Produk Jurnalistik Pada Kantor Media Harian Kepri.Com - Yuliani, Yani; Syahrinullah, Syahrinullah (Journal of Management Branding, 2025)
Information is something very important in life, various sources of information can be easily obtained today. The main issue in this study is the varying quality of writing among journalists and online media reporters, which results in the need for multi-level editing before the news is aired. In addition, the selection of news headlines that have not been properly controlled can also reduce the quality of journalistic products. The purpose of this study is to analyze editorial management in improving the quality of journalistic products at the Riau Islands Daily media office. Locus This research was carried out in the editorial environment of HarianKepri.com media, with the aim of producing good journalistic products, starting from data collection, news/issues, journalist interview techniques with sources. News writing and presentation techniques. The research method used is a qualitative method. Data collection through interviews, observation and documentation. Four research informants represent the editor-in-chief, editors, and journalists who are responsible for the Hariankei  media as well as the company's leaders who are responsible for the company's human resources. The results of the research are the formation of an ecosystem, work patterns, standard operating procedures (SOP) to produce good journalistic/news results, accurate and reliable news